The historical politics of the juvenile justice system and the operation of law in the juvenile court in Istanbul in regard to property crimes - Kurtege, Bengü. (Thesis (M.A.)-Bogazici University.Atatürk Institute for Modern Turkish History, 2009., 2009)
This thesis is on the historical transformations in juvenile justice policy in relation to property crimes and the operation of law in the one of the juvenile courts in Istanbul. The politics of the Penal Code and the legal techniques to handle juvenile delinquency in different conjunctures are explored. The cooperation between the juvenile court, social work and state administered child care centers to correct the child characterizes the legal politics in the succumbed welfare era whereas the new juvenile justice policy is double sided. It targets both the security of the victims and the rehabilitation in an open milieu by means of the new partnership between civil society, the court and the family. The operation of law is also scrutinized. The judges’ visions on the function of law and juvenile justice policies explain their visions as the major operators of the law. Both (un) successful patterns in verbal and bodily performances in the courtroom and fight by words in the court records show us the contestations in the legal arena. The scrutiny of these performances and the tactics in official documents unpack the reception of law by the offenders, the operation of law from below, to renegotiate the limits of legitimacy. Juvenile delinquents’ tactics are categorized as “legitimizing theft as a channel for survival” and “blaming people who subject them to violence.” Interviews with three judges, attendance at thirty-four property crime trials and twenty-five files obtained in my field research between February, 2008 and June, 2008 constitute the primary resources.
Keywords: Juvenile justice, Administration of -- Turkey.; Juvenile courts -- Turkey.